Development of Functional Arabic Grammar (Nahwu) Textbooks Based on Local Wisdom for Arabic Language Students - Nur Azizah, Fina; Nashoih, Afif Kholisun (Institut Agama Islam Negeri Curup, 2024)
This research is motivated by the assumption that Arabic itself is one of the Semitic language families that is considered difficult to learn, because it has a complex grammar. Likewise, learning resources, teaching materials, textbooks and also nahwu books are known to be traditional, thick, and a little boring because they are only in the form of writing, and less interesting to learn. On the other hand, many students do not know about the local wisdom of the Indonesian nation, because as long as they learn Arabic, they only learn about the language of foreign nations. Therefore, this research aims to develop a Grammatical Arabic Functional textbook based on Local Wisdom for Arabic language learners. The method used in this study is R&D by adopting the Borg and Gall development model. The results of this study in the form of an assessment from experts stated that this book was categorized as very feasible, with a percentage of scores of 83% from material expert validators, and 100% from media expert validators. While the results of field trials stated that this textbook was able to improve student learning outcomes, which can be seen from the pre-test results of 50.4 and post-test scores of 85.2. So it is known that there is a difference of 34.8 which shows a significant increase. Therefore this textbook is able to improve understanding of the Arabic language, especially nahwu.